Documentos de procedencia jesuítica en la colección de papeles varios del archivo universitario de Salamanca - Vivas Moreno, Agustín (Revista General de Información y Documentación, 2010)
The main aim of this article is the analysis of the documentation of Jesuit origin located on the “Papeles Varios” Collection of Salamanca’s University Archive. This documentary collection has a great importance due to its quite interesting unpublished materials and it deserves being consulted for historical studies on 16th to 18th centuries. After analysing the several documentary origins, the origin of Jesuit documentation is studied thoroughly. So its installation units are examined and a chronological, topographic and idiomatic analysis of those documents is built. We conclude with a diagnosis about the contents and the importance of these documents for historic research. In short, through this research we will update the sources for studying the Jesuits in documentary and bibliographic university batches and in the context of the Hispanic Monarchy of 16th to 17th centuries. This whole research is registered on a wider project about identification and description of batches in University Archives.